Satu Tungku Tiga Batu, Toleransi Hidup Beragama Masyarakat Fak-Fak: Tinjauan Ensiklik Fratelli Tutti - Hendrik Ryan Renna (CENDERAWASIH: Jurnal Antropologi Papua, 2021)
The purpose of this study is that the author wants to observe and analyze the extent to which the concept of religious tolerance is practiced in everyday life in a pluralistic society. Of course, one must have a special guideline that is used as a philosophy of living together, for example the philosophy of Satu Tunku Tiga Batu, present as a life guide for the Fak-Fak community in building the beauty of tolerance in religious relations which is also seen from the Fratelli Tutti Encyclical as a new ideology juxtaposed with traditional philosophy. which produces a common ground that teaches each individual to appreciate and appreciate the differences in society. The method used is a qualitative method through the process of obtaining data from literature studies and also the results of analysis from several related sources in order to obtain accurate data. From the results of this study, the researchers found that religious tolerance is basically a form of solidarity with others who appreciate that human life is equal to each other in the eyes of God even though they have different religious backgrounds, but must be able to show effective relationships between one religion and another.